Shadow Medicine : The Placebo in Conventional and Alternative Therapies - JOHN S. HALLER JR (Columbia University Press, 2014)
consider for a moment these varying scenes: a graduate of Barbara Ann Brennanâ€™s School of Healing draws upon the forces in the universe to balance the multilayered fields of aura emanating from a patient; a homeopath, after a lengthy consultation, treats the symptoms of alopecia with sulfur serially diluted and succussed to 30Â°C to release its dynamized energies; a nurse creates an energy exchange using therapeutic touch to restore a patientâ€™s self-healing abilities; and, finally, a chiropractor applies spinal manipulative therapy to treat a child with attention deficit hyperactive disorder. Each of these modalities is representative of unconventional healing practices common across the United States. Whereas reductionist biomedicine draws its authority from the randomized clinical trial (RCT) and laws embedded in the natural sciences, these and other unconventional therapies rely on a philosophy of organism known as â€œvitalism,â€ which explains life not by the laws of physics and chemistry, but by a principle, force, or spiritlike power that comes from beyond the material world to animate organic matter